Analisis Perencanaan Dan Evaluasi Anggaran Dalam Meningkatkan Kinerja Pemerintah Daerah Kabupaten Aceh Singkil - Hendrawan, Teuku Rully; Sihombing, Marlon; Lubis, Maksum Syahri (Universitas Medan Area, 2021)
This study aims to determine and analyze budget planning and evaluation in improving the performance of the Aceh Singkil District Government, and to find out and analyze the obstacles faced in planning and evaluating budgets in improving the performance of the Aceh Singkil District Government. Research informants were selected by purposive sampling. Data collection techniques used through interviews and observation. Data analysis techniques used in this study are qualitative data analysis techniques. The results of the study indicate that budget planning and evaluation in the Aceh Singkil District Government has not fully been able to improve budget performance, especially financial planning, the most recent data collection for performance evaluation and efforts to overcome budget constraints. The obstacle factor in planning is that there is a tendency to reduce budget allocations for certain activities with the aim that the available budget can be allocated to various other programs, and the inventory money requirement for a one-month period is not well planned. Whereas the constraints in the performance evaluation, data or information available have not fully been able to show the most recent conditions, because there is a possibility that the stages of activities carried out have not been reported, or there is a possibility that the evidence of expenditure has not been recorded because it still can be administered.